2001
DOI: 10.1046/j.1526-0968.2001.005001022.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Delivery in a Pregnant Woman with Lupus Anticoagulant Positive Systemic Lupus Erythematosus Treated with Double Filtration Plasmapheresis

Abstract: The case was a 29 year old female who has suffered from systemic lupus erythematosus (SLE) since 15 years of age. The activity of SLE was low, and she took prednisolone orally. Her first pregnancy failed after 14 weeks. In the second pregnancy, she had thrombocytopenia, prolonged activated partial thromboplastin time (APTT), positive lupus anticoagulant (LAC) and thus was diagnosed with antiphospholipid antibody syndrome (APS). Combination therapy with steroids and aspirin was started, and she underwent treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…However, in autoimmune diseases, plasmapheresis may lead to a rebound overproduction of the same antibodies and require intensified treatment [7]. Similar results were obtained in the report by Takeshita et al [11]. They started a combination therapy of steroids and aspirin, as well as double filtration plasmapheresis, in the early stage of pregnancy in a patient with APS.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, in autoimmune diseases, plasmapheresis may lead to a rebound overproduction of the same antibodies and require intensified treatment [7]. Similar results were obtained in the report by Takeshita et al [11]. They started a combination therapy of steroids and aspirin, as well as double filtration plasmapheresis, in the early stage of pregnancy in a patient with APS.…”
Section: Discussionsupporting
confidence: 53%
“…Because plasmapheresis physically removes antibodies and their end products it has been used for successful treatment of several conditions including HELLP syndrome, thrombotic thrombocytopenic purpura, cryoglobulinemia [7], and catastrophic APS [8]. Several case reports have suggested that plasmapharesis may also be a successful treatment for pregnant women with APS [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…The ef cacy of DFPP in pregnant women with APS 14 and noncatastrophic APS 15 has already been described. Not only the level of aCL but also that of LAC will be expected to diminish with DFPP and the short-term ef cacy of DFPP will be superior to that of IAPP in this regard.…”
Section: Discussionmentioning
confidence: 94%